Renewable Energy Consumption and Unemployment in South Africa - Khobai, Hlalefang; Kolisi, Nwabisa; Moyo, Clement; Anyikwa, Izunna; Dingela, Siyasanga (International Journal of Energy Economics and Policy, 2020)
The importance of renewable energy consumption has grown to a large extent over the recent years. The benefits of renewable energy consumption ranging from improved environmental quality to higher economic growth are well documented. However, the impact of renewable energy consumption on unemployment has received relatively less attention. This study examines the relationship between renewable energy consumption and unemployment in South Africa over the period 1990-2014. The Autoregressive Distributed Lag (ARDL) model was employed to test the long-run and short-run impacts of renewable energy consumption on unemployment. The results reveal that renewable energy consumption has a negative and significant effect on unemployment in the long-run. However, in the short-run the variables have an insignificant relationship. The study therefore advocates for an increase in the production and consumption of renewable energy in order to boost employment levels. Keywords: Renewable energy consumption, unemployment, ARDL, South Africa JEL Classifications: Q20; C50 DOI: https://doi.org/10.32479/ijeep.6374